Narrativa transmedia ante la gestión de medios - Jiménez Carrión, Cristhian Rene (2022)
Transmedia narrative in journalism has led communication companies to develop different projects based on the same content that is related to each other, published on different platforms, taking advantage of the particularities of each one of them to increase interaction with users. Given this, it was established as a general objective to propose a transmedia narrative before the management of the media to position the news section of the Ecuavisa digital platform. The methodology used was a qualitative approach, the type of research applied was descriptive, exploratory, bibliographic and field, as a data collection instrument semi-structured interviews were used aimed at a specialist in the subject and those in charge of developing content on the digital page of Ecuavisa. The results showed that the program on which the pilot plan was focused was on the Televistazo newscast, where different segments are promoted using the reel format of the Instagram social network, it was successful due to the large number of views by the audience. One of the main strategies used in the presentation of news (with an understandable and digital language) is attributed to the multiplatform narrative that encouraged sharing or replicating the stories on different social networks and generating comments on their publications. It is concluded that social networks and other platforms such as YouTube are an important tool to generate transmedia content in traditional media.